Financial education among higher education students in Huánuco - Chahua-Salcedo, Melina (2025)
The general objective of this study was to analyze the level of financial literacy among higher education students in Huánuco, 2024. The methods included a quantitative and descriptive approach to analyze university students' financial literacy. The sample included 184 university students from the Faculty of Economics who were administered a prototype Likert test. The findings revealed that economics students have considerably good financial literacy, representing 83.2% of the respondents, meaning that the vast majority of students have a satisfactory level of proficiency. In conclusion, the study revealed that students from the Faculty of Economics have considerably good financial literacy. This adequate, but not outstanding, level could impact their ability to make appropriate financial choices both in their professional careers and in their daily lives; in turn, it could impact their financial security, investment choices, and future savings.